Extracellular Pectinase Production By Free And Calcium Alginate Immobilized Cells Of Enterobacter Aerogenes Nbo2 - Magalinggam, Nisha (2013)
Currently industrial enzymes are used widely in Malaysia for its vast range of importance. However the lack of locally produced industrial enzymes has increased the budget of Malaysia for industrial sector in order to import them from other countries. Pectinase is one of the industrial enzyme which is widely used in juice and wine industries. The present study was carried out to screen for the potential local bacterial pectinase producers. Isolate NBO2 was chosen based on its screening result (1.89 ± 0.23 U/ml pectinase) and was identified as Enterobacter aerogenes NBO2 by morphology, biochemical and molecular identification. This study was focused on the physiochemical improvements of pectinase in a flask system with free cells and immobilized cells of E.aerogenes entrapped in calcium alginate beads. The improved reaction conditions for pectinase production with free cells were initial medium pH of 6.5, cultivation temperature of 37ºC, inoculum size of 3.0% (v/v; 2.7x109 cells/ml), agitation speed of 250 rpm, 1.5% (w/v) of pectin as a sole carbon source and 0.26% (w/v) of yeast extract as the nitrogen source. The pectinase production was 18.539 U/ml with the improved condition. There was an increment of 2949.18% compared to the activity before improvement. In order to improve the pectinase production, the physical enhancement of pectinase was carried out with immobilized cells of E.aerogenes NBO2 in calcium alginate. The improved reaction conditions with immobilized cells of E.aerogenes were calcium alginate beads with 5% (w/v) concentration, inoculums size of 4% (v/v; 9.3x108 cells/ml), 10 beads and agitation speed of 250 rpm. The pectinase production was 23.478 U/ml which increased about 26.64% compared to the improved condition with free cells of E.aerogenes NBO2.